Analisis Kebijakan Pemberian Bantuan Militer Amerika Serikat kepada Ukraina Selama Masa Invasi Rusia 2022 - Alifiobono, Adeva; Anam, Syaiful; Sabilla, Kinanti Rizsa (Department of International Relations, University of Mataram, 2023)
This study aims to analyze the policy of providing United States military assistance to Ukraine during the 2022 Russian invasion. The policy of the United States deciding to provide military assistance to Ukraine to help Ukraine resist the Russian invasion drew reactions from the international community as well as from Russia itself. This study aims to analyze this in the context of: exploring the types of assistance, the reasons & objectives behind policy making, and their implications for the relationship between the United States and Russia. This study will use the Rational Actor Model Theory to analyze the reasons behind the policy of granting military to Ukraine by the United States which has considered all available viewpoints, alternatives, and solutions so as to achieve the highest objectives of the policy. In looking at the goals to be achieved by the United States in policy making, the concept of national interest will provide insight into what the United States’ intended goals behind their policy of providing military assistance to Ukraine. The results indicate that the given aid is an investment whose benefits outweighs its costs, as well as the United States justifying their aid provision to Ukraine under defense, ideological and economic interests